The Most Important Measures in Reducing Infection Control in the Anesthesia Work Environment: An Evidence-Based Study - Younes Barazesh; Parisa Moradimajd; Azam Saei; Jamileh Abolghasemi; Mohammad-Mahdi Azizi-Darbandi (Archives of Anesthesia and Critical Care)
Background: Anesthesia providers cross-contaminate their work environment. The hands of anesthesia providers are vectors for the transmission of infection between medical equipment in the anesthesia work environment and patients. The high work density of anesthesia providers around the patient has made it important to monitor infection control in the work environment and anesthesia procedures. This research aimed to find the best evidence for preventing or reducing infection in the anesthesia work environment. Methods: The measures required for the guidelines in the field of infection control in the anesthesia work environment were determined according to the available resources and the use of expert opinions of anesthesiologists and faculty members. Then, the guidelines for infection control in the anesthesia work environment were designed based on the evidence-based method (Stettler model). Also, it has been implemented in a limited way in the operating room. To assess the validity of the approach used in calculating the content validity coefficient (CVR) and the content validity index (CVI), Finally, the Test-Retest method, and Cronbach's alpha coefficient were used to determine reliability. Results: The guidelines for infection control in the anesthesia work environment were designed using evidence-based methods (Stettler's model). The content validity of anesthesia procedures requiring infection control guidelines was reported with a content validity index (CVI) of more than 0.79 and a content validity ratio (CVR) of more than 0.59. The reliability test was measured by Cronbach's alpha coefficient (0.806). Conclusion: Based on this study, the use of global infection control guidelines changes the attitude of anesthesia nurses and reduces the rate of infection in the anesthesia work environment. Also, the use of evidence-based methods facilitates the implementation of guidelines in the target environment.